Mortgage indebtedness and household financial distress - Dimitris Georgarakos; Adriana Lojschova; Melanie Ward-Warmedinger (Institute for the Study of Labor (IZA), 2009)
Using comparable survey data from twelve European countries we investigate households' attitudes towards mortgage indebtedness. We find that a given debt burden creates much higher distress in Southern countries, France and Belgium, where fewer households have a mortgage outstanding relative to countries where a sizeable part of the population uses mortgage debt, like the UK, the Netherlands, and Denmark. This is the case after taking into account ppp-adjusted income levels, a rich set of socioeconomic characteristics, housing traits, country-specific constant terms, and household unobserved heterogeneity. We attribute part of this asymmetry to cross-country differences in the expansion of credit markets, which facilitate differential access to liquidity. Household's reported distress is also affected by excess indebtedness relative to the debt load of reference households, and crucially so in countries with less expanded mortgage markets. Thus it appears that households evaluate their own debt burden partly in comparison with the debt position of their peer group and in a way consistent with social stigma considerations which lessen in significance as markets expand. Households' assessment of a debt burden therefore tends to diminish in more expanded credit markets and this process can be reinforced by reference to other households in a growing pool of debt holders.
Keywords: D12; D14; G21; 330; Mortgage debt; credit markets; financial distress; household finance; peer effects; Hypothek; Private Verschuldung; Verschuldungsrestriktion; Soziale Beziehungen; Kreditmarkt; Marktliquidität; Europa